Pemberdayaan Kemitraan Masyarakat untuk Meningkatkan Kualitas Proses Produksi dan Pemasaran Jamur Tiram pada Kelompok Tani Trah Tiram Mandiri di Parungkuda - Casban Casban; Nur Asni Gani; Umi Marfuah; Athifah Silmi Hapsari; Sebriana Sobariah (Warta LPM, 2024)
Community Partnership Empowerment (CPE) as the topic of community service activities in the Community Based Empowerment scheme with partners, namely the Mandiri Tiram Farmers group located in Parungkuda. The objectives of CPE are (1) Providing solutions to problem solving aspects of production using technology to increase partner income by 10%. (2) Assistance in developing marketing strategies by utilizing communication and information technology to expand the market. Implementation of activities through the stages of socialization, discussion, asset handover, mentoring and evaluation. The results of PKM activities can provide solutions in the production aspect by providing assistance with sterilization process equipment to improve the quality of making mushroom seeds (baglog). Press machine assistance to maintain consistent baglog density and increase production capacity. Assistance activities in developing marketing strategies by providing knowledge and skills in the use of information communication technology, packaging label designs and processed mushroom food products. The output of CPE activities is an increase in sales turnover of oyster mushrooms from Rp. 19,800,000/month to Rp. 21,780,000/month or 10% for 1 production period can be achieved successfully by applying technology in the production process of making mushroom seeds.